2015
DOI: 10.1038/srep15331
|View full text |Cite
|
Sign up to set email alerts
|

A new nanoscale metastable iron phase in carbon steels

Abstract: Metastable ω phase is common in body-centred cubic (bcc) metals and alloys, including high-alloying steels. Recent theoretical calculations also suggest that the ω structure may act as an intermediate phase for face-centred cubic (fcc)-to-bcc transformation. Thus far, the role of the ω phase played in fcc-bcc martensitic transformation in carbon steels has not been reported. In previous investigations on martensitic carbon steels, extra electron diffraction spots were frequently observed by transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 51 publications
3
28
0
Order By: Relevance
“…This energy difference between the ω structure and the state in experiments is much larger than those for the group 4 elements, which implies that the ω structure of Fe is thermodynamically more difficult to be formed than that of the group 4 elements. In contrast, several experimental reports have claimed that the ω structure can be formed in Fe-based alloys [16,17]. In these experiments, the ω structure has been observed at twin boundaries of the BCC or as precipitates in the BCC matrix.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This energy difference between the ω structure and the state in experiments is much larger than those for the group 4 elements, which implies that the ω structure of Fe is thermodynamically more difficult to be formed than that of the group 4 elements. In contrast, several experimental reports have claimed that the ω structure can be formed in Fe-based alloys [16,17]. In these experiments, the ω structure has been observed at twin boundaries of the BCC or as precipitates in the BCC matrix.…”
Section: Resultsmentioning
confidence: 88%
“…In addition, it has been reported that the ω structure is formed in elemental Ta and Ta-W alloys by applying shock pressure [14] and in elemental Mo after high-pressure torsion [15]. Several experimental reports have recently claimed that the ω structure can be found also in steels, i.e., Fe-Cbased alloys [16,17]. Structures based on the ω lattice, where constituent elements occupy the same atomic sites as the ω structure with atomic orderings, have also been observed in experiments for alloys such as Cu-Zn [18], Cu-Mn-Al [19], Ni-Al [20], Fe-Ni-Co-Mo [21], Fe-Mn-Co-Mo [22], and Fe-Ni-Mo [23] alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, our study confirms the importance of other alloying elements apart from C in stabilizing the ω phase in steel, in concurrence with other experimental studies. [2] This trend has also been observed in DFT calculations of the cohesive properties of Ru and Pd in the ω-Fe supercell. [1] To gain further insight into the observed energy trends, we have calculated the spin-polarized density of states (DOS) of ω-Fe supercells.…”
Section: Experimental Methodssupporting
confidence: 61%
“…TEM observations revealed that ultra-fine ω-Fe 3 C particles exist at twinning boundary region in twinned Fe-C martensite, and the ω-Fe 3 C has a hexagonal crystal structure with lattice parameters of a = a ω = 2a α-Fe = 4.033 Å, c ω = 1/2 × 3 a α-Fe = 2.47 Å for a α-Fe = 2.852 Å 31,33,[35][36][37][38] . The ω-Fe 3 C unit cell structure can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Metastable hexagonal ω-Fe 3 C phase particles, which are 1 to 2 nm big in size, distribute only at the body-centered cubic (BCC) {112}<111>-type twinning boundary region in twinned high-carbon Fe-C martensite [33][34][35][36][37][38][39][40] . It was observed by in-situ heating transmission electron microscopy (TEM) that these twinning boundary ω-Fe 3 C particles eventually transformed into θ-Fe 3 C carbides [41][42][43][44] .…”
mentioning
confidence: 99%